Rancang Bangun Media Pembelajaran E-Learning Di SMK Negeri 1 Majalengka - Metta Mariam (Media Aplikom, 2021)
E-learning allows the educational process without going through face to face directly and the delivery of knowledge to students can be done easily. Many educational institutions or schools that have implemented e-learning learning. In this study, e-learning learning media will be built at SMK 1 Majalengka and find out the feasibility of this e-learning learning media at the school. The method used in this study uses the ADDIE development model, namely: (1) Analysis, (2) Design, (3), Development, (4) Implementation, and (5) Evaluation. The assessment will be carried out by media experts and material experts with the data collection technique used is a questionnaire technique to obtain quantitative data as primary data and qualitative data in the form of suggestions or comments as data for improving e-learning. The quantitative data obtained are then converted to qualitative data using ideal assessment criteria. The results obtained showed that: (1) e-learning was successfully developed through each stage of ADDIE; (2) E-learning developed has online class features that are used as a medium of practice and distance learning instead of when the teacher is unable to attend class; (3) E-learning has "Very good" criteria from media experts with an average rating of "4,24"; (4) E-learning has "Very Good" criteria from material experts with an "4,2" rating. Based on the results of the assessment obtained it can be concluded that the design of e-learning media learning in SMKN 1 Majalengka is feasible to be developed and used